An Application Domain Based on General Object Oriented Software Models (Journal of the College of Education for Women, 2019)
Any software application can be divided into four distinct interconnected domains namely, problem domain, usage domain, development domain and system domain. A methodology for assistive technology software development is presented here that seeks to provide a framework for requirements elicitation studies together with their subsequent mapping implementing use-case driven object-oriented analysis for component based software architectures. Early feedback on user interface components effectiveness is adopted through process usability evaluation. A model is suggested that consists of the three environments; problem, conceptual, and representational environments or worlds. This model aims to emphasize on the relationship between the objects and classes in the representationalmodel and the elements in the considered system. Implementing this model on some practical examples is investigated and resulted into promising improvement in software design and understanding.